The Effects of Personality, Self-Efficacy, and Locus of Control on The Success of Javanese Female Merchants In Surabaya - Dewi Urip Wahyuni; Nur Laily (School of Business, IPB University (SB-IPB), 2020)
The study aimed to examine the effect of personality on self-efficacy, locus of control, and the success of Javanese female merchants in the modern market, Surabaya, Indonesia. Questionnaire was used as a research instrument in this study. This study involved 100 Javanese female merchants as respondents. The samples were collected through a non-probability sampling technique. The data were analyzed based on Partial Least Square analysis using Smart PLS software. The findings of this study indicated that all five research hypotheses proposed in this study were accepted. First, personality affected self-efficacy. Second, personality affected the locus of control. Third, personality affected the success of the Javanese female merchants. Fourth, self-efficacy affected the success of the Javanese female merchants and the locus of control affected the success of Javanese female merchants in the modern market, Surabaya, Indonesia. Keywords: personality, self-efficacy, locus of control, Success, Javanese female merchants